Identification of Major Effect QTLs for Agronomic Traits and CSSLs in Rice from Swarna/Oryza nivara Derived Backcross Inbred Lines - Surapaneni, Malathi; Balakrishnan, Divya; Mesapogu, Sukumar; Addanki, Krishnam Raju; Yadavalli, Venkateswara Rao; Tripura Venkata, V. G. N.; Neelamraju, Sarla (Frontiers in Plant Science, 2017)
Backcross inbred lines (BILs) derived from elite x wild crosses are very useful for basic studies and breeding. The aim of this study was to map quantitative trait loci (QTLs) associated with yield and related traits and to identify chromosomal segment substitution lines (CSSLs) from unselected BC2F8 BILs of Swarna/Oryza nivara IRGC81848. In all, 94 BILs were field evaluated in 2 years (wet seasons, 2014 and 2015) for nine traits; days to 50% flowering, days to maturity (DM), plant height (PH), number of tillers, number of productive tillers, panicle weight, yield per plant, bulk yield, and biomass. BILs were genotyped using 111 polymorphic simple sequence repeats distributed across the genome. Fifteen QTLs including 10 novel QTLs were identified using composite interval mapping, Inclusive composite interval mapping and multiple interval mapping (MIM). O. nivara alleles were trait-enhancing in 26% of QTLs. Only 3 of 15 QTLs were also reported previously in BC2F2 of the same cross. These three included the two major effect QTLs for DM and PH detected in both years with 13 and 20% phenotypic variance. Further, a set of 74 CSSLs was identified using CSSL Finder and 22 of these showed significantly higher values than Swarna for five yield traits. CSSLs, 220S for panicle weight and 10-2S with consistent high yield in both years are worthy of large scale field evaluation. The major QTLs and 22 significantly different CSSLs are a useful resource for rice improvement and dissecting yield related traits.